Economic Feasibility and Risk Assessment of Patin Aquaculture Agribusiness in Kampar Regency, Riau, Indonesia - Cemda, Abdul Rahman (Global Insights in Management and Economic Research, 2025)
Purpose: This study evaluates the economic feasibility and assesses the financial risks associated with smallholder patin (Pangasius hypophthalmus) aquaculture in Kabupaten Kampar, Riau Province, Indonesia, to provide evidence-based recommendations for sustainable aquabusiness development. Materials and Methods: A descriptive-quantitative research design was employed with 60 smallholder patin farmers selected through purposive sampling. Data collection involved structured interviews, production record audits, financial document analysis, and direct pond observations. Economic feasibility was evaluated using Net Present Value (NPV), Benefit-Cost Ratio (BCR), Internal Rate of Return (IRR), and Payback Period (PP) at a 10% discount rate. Risk assessment incorporated Coefficient of Variation (CV), sensitivity analysis, Monte Carlo simulation (10,000 iterations), and scenario analysis. Statistical analysis was performed using SPSS 26. Results: The average NPV was IDR 127,450,000 (USD 8,497), BCR was 1.34, IRR was 24.6%, and PP was 2.8 years, indicating economic viability. Risk analysis revealed a CV of 0.42, suggesting moderate income variability. Monte Carlo simulation showed a 73.4% probability of positive returns. Sensitivity analysis identified feed cost (elasticity coefficient: -0.68) and market price (elasticity coefficient: 0.82) as critical risk factors. Under pessimistic scenarios, 31.7% of farms showed negative NPV. Conclusions: Patin aquaculture demonstrates economic feasibility under current market conditions, but faces significant risks from feed cost fluctuations and price volatility. Risk mitigation strategies including feed cost management, market diversification, and insurance mechanisms are recommended for sustainable development.